Dengue and dementia risk: A nationwide longitudinal study. Issue 5 (November 2021) - Chu, Che-Sheng; Tsai, Shih-Jen; Cheng, Chih-Ming; Su, Tung-Ping; Chen, Tzeng-Ji; Bai, Ya-Mei; Liang, Chih-Sung; Chen, Mu-Hong
Highlight: Higher risk by 2.23-fold of dementia was found in patients with dengue. The higher risk was found in patients with dengue for Alzheimer's disease and unspecified dementia. No higher risk was found in patients with dengue for vascular dementia. The risk of dementia significantly increased in both male and female patients with dengue. The E-values support the association between dengue and dementia risk. Abstract: Background: Accumulating evidence suggests neurological manifestations after dengue infection. However, the relationship between dengue and long-term neurocognitive sequel remains unclear. Methods: We recruited 816 patients with dengue and 8, 160 controls between 1997 and 2012 using data from Taiwan National Health Insurance Research Database and followed them up until the end of 2013. Individuals who exhibited any type of dementia were identified during the follow-up period. Cox regression analyses were performed with adjustments for demographic data and medical and mental comorbidities (cerebrovascular diseases, traumatic brain injury, hypertension, dyslipidemia, diabetes mellitus, depression, alcohol use disorder, and substance use disorder). The E-value for the causality of the evidence was calculated. Sensitivity analysis was conducted to exclude patients with prodromal dementia. Results: Patients with dengue were more likely to develop dementia (hazard ratio [HR]: 2.23, 95% confidence interval [CI]: 1.51–3.28), Alzheimer's disease (HR: 3.03, 95% CI: 1.08–8.45), and unspecified dementia (HR: 2.25, 95% CI: 1.43–3.53), but not vascular dementia compared to controls during the follow-up period. Sensitivity analyses after exclusion of the observation period over the first three years or first five years and after exclusion of patients' enrollment before 2010 or 2008 showed consistent findings. The E-values for the HR (range 3.62–5.51) supported the association between dengue and subsequent dementia among the whole population, men, and women. Conclusion: The risk of dementia was 2.23-fold higher in patients diagnosed with dengue during the follow-up period than in the controls. Further studies are necessary to investigate the underlying pathophysiology of dengue and dementia.